Processing-controlled suppression of Lüders elongation in AlMgMn alloys. (June 2019) - Ebenberger, P.; Uggowitzer, P.J.; Kirnstötter, S.; Gerold, B.; Zaefferer, S.; Pogatscher, S.
Abstract: The Lüders elongation, ε L, its dependence on grain size, and its processing-controlled suppression are examined on several AlMgMn alloys. We found that grain size variations result in a Hall-Petch-type ε L relation. We interpret the increase in macroscopic flow stress upon ε L as a transitional increase in the activation stress of dislocation sources, expressed by an additional term of the Hall-Petch coefficient. The decisive measure for suppressing ε L is based on the formation of non-aged dislocations. We demonstrate that these can be created intrinsically by utilization of the difference in the thermal expansion of matrix and primary constituents upon quenching. Graphical abstract: Unlabelled Image